AI IN LEARNING LANGUAGES - Qodiriy Mahzuna; Panjiyeva Ruxsora Dilmurodovna (“SUN’IY INTELLEKTNING TIL O‘RGANISHDAGI O‘RNI” MAVZUSIDA TALABALAR ILMIY-AMALIY KONFERENSIYASI, 2025)
This article explores the role of artificial intelligence (AI) in language learning and education. It discusses how AI tools like adaptive learning systems, virtual tutors, and speech recognition apps personalize and improve learning experiences. The author combines personal experiences with references to recent studies to highlight both the benefits and limitations of AI, such as lack of cultural understanding and overdependence risks. The article concludes that the best approach is a blend of AI tools and human teaching to maximize language learning outcomes.